(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study was to assess the effect of ethanolic extract of Syzygium aromaticum(clove) buds in alcohol induced hepatotoxicity in rats. Study Design: Randomized controlled trial Place and duration of study: Department of Pharmacology, Fatima Memorial College of Medicine and dentistry, Lahore from 1st July 2011 to 31st December 2011. Materials and Method: The rats were divided into five groups, i.e. control group (A), ethanol positive group (B), experimental groups (C and D) and standard group (E). Group C experimental rats received ethanol (3 g/kg body weight daily intraperitoneal injection) and ethanolic extract of Syzygium aromaticum at 250mg/kg of body weight daily orally for a period of forty five days. Group D experimental rats received ethanol and ethanolic extract of Syzygium aromaticum at 500 mg/kg of body weight. Group E received ethanol and silymarin (100mg/kg orally).Blood samples were taken at 45th day and liver in each was taken out for histopathological examination. Results: The ethanol group rats showed variable increase in serum ALT (Alanine Transaminase ), AST(Aspartate transaminase)), ALP(Alkaline Phosphatase) and total bilirubin levels. In group C and group E rats the levels of these parameters become slightly decreased while in group D rats the levels decreased more towards normal. The morphological examination of experimental groups C and E rats showed slight recovery whereas the rats in experimental group D showed a significant recovery. Syzygium aromaticum constituents, especially flavonoids and polyphenols have strong anti-oxidant activity which provides hepato-protection against alcohol induced hepatotoxicity. Conclusion: High dose of Syzygium aromaticun ethanolic extract (500 mg/kg body weight) showed better hepatoprotection against alcohol induced hepatotoxicity than low dose Syzygium aromaticum extract and silymarin in rats.